(untitled) (Zoo Botanica, 2025)
The population dynamics of Monotheca buxifolia, commonly known as Gurgura, were investigated in the sub-tropical broad-leaved evergreen forests of district Mohmand, Khyber Pakhtunkhwa (KPK). This study aimed to assess the economic and medicinal potential and to determine the loss due to deforestation of M. buxifoliain in Sub-tropical Broad leave Evergreen Forest. The economic evaluation focuses on the commercial prospects of M. buxifolia. This study analyzed M. buxifolia as an oil-rich fruit for potential industrial use. This study gauges the feasibility of sustainable economic ventures associated with this species by examining market trends, supply chains, and demand dynamics. Simultaneously, the study delves into the medicinal potential of M. buxifolia, investigating its traditional uses and modern medical applications. Traditional practices also reveal that M. buxifolia played a significant role in veterinary medicine for anti-helminthic applications. The plant’s various parts, including leaves, bark, and fruits, are traditionally believed to possess therapeutic properties such as antioxidants. Market surveys and value chain analysis were done in the study area to meet the objectives of phytochemical analysis. The satellite data for deforestation was downloaded from ArcGIS software. To obtain information about topographic parameters like slope and elevation, (DEM) Digital Elevation Model was used. The key findings are M. buxifolia provides a reliable source of income and cash flow for local communities. The fresh fruit contains citric acid, ascorbic acid and sugar. This suggests that the fruit has a relatively high concentration of sugars, which could contribute to its sweetness and energy content